2009
DOI: 10.1080/13658810802084806
|View full text |Cite
|
Sign up to set email alerts
|

Address databases for national SDI: Comparing the novel data grid approach to data harvesting and federated databases

Abstract: The original purpose of addresses was to enable the correct and unambiguous delivery of postal mail. The advent of computers and more specifically geographic information systems (GIS) opened up a whole new range of possibilities for the use of addresses, such as routing and vehicle navigation, spatial demographic analysis, geo-marketing, and service placement and delivery. Such functionality requires a database which can store and access spatial data effectively. In this paper we present address databases and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 14 publications
0
17
0
1
Order By: Relevance
“…The original address can be divided into some address elements, t means that the address element can be identified and x means that the address cannot be identified. We can calculate the matching degree from Equation (1).…”
Section: Experiments and Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The original address can be divided into some address elements, t means that the address element can be identified and x means that the address cannot be identified. We can calculate the matching degree from Equation (1).…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…The proposed methods are intended to: (1) adapt to the complexity of Chinese text; (2) account for the topological relationships among address elements; and (3) improve the efficiency and accuracy of traditional geocoding algorithms. In the remainder of this paper, we first describe the study area and data in section 2, followed by the optimized method in detail, including the structure of the address model and the address standardization and address matching process in Section 3.…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…The other option (b) is to have a distributed, i.e. federated, architecture (Coetzee and Bishop, 2009), in which each department has its own database and where the databases are connected to a central data and document catalog. This later option implicates that in each department sits at least one person that is responsible for data and documents at the department level.…”
Section: Context Of Implementationmentioning
confidence: 99%
“…The data grid approach deviates from the centralized approach in the other models and this makes it suitable for SDIs that are currently evolving towards more distribution and more dynamism. The evaluation showed that where a large number of organizations with multiple heterogeneous address datasets are involved with no single organization tasked with the management of a national address database, the data grid approach has some unique features that make it an attractive alternative to the other models [14].…”
Section: Introductionmentioning
confidence: 99%